OPTIMIZATION OF ONLINE LEARNING IN BLANKSPOT AREA - Julianta, Ifan Julianta (JURNAL SOCIUS, 2023)
The purpose of this study was to determine the optimization of online learning in the Blank Spot area at SMP Negeri 2 Pulau Hanaut. This study uses a qualitative approach. The research subjects in this study were 2 teachers of class VII and VIII, at SMP Negeri 2 Pulau Hanaut while the informants were 2 (two) students of class VII and VIII. Online learning uses learning media in the form of the Whatsaap application and LKS which for Whatsapp itself is the media used by the teacher to interact with students as well as information from the teacher to students, especially in social studies learning which is carried out at SMP Negeri 2 Pulau Hanaut. While the LKS media is the media used by the teacher in determining the material discussed and giving assignments by the teacher to students. Optimization of Online Learning in Blank Spot Areas at SMP Negeri 2 Pulau, one of which is a wifi kiosk facility that provides paid wifi facilities as well as wifi facilities in schools that can be used free of charge by students even though they are used interchangeably. Implementation of online learning conducted at SMP Negeri 2 Hanaut Island has obstacles including: The location of the school which is in the Blank Spot area, Frequent power outages in the village resulting in dead Wifi access, a small number of students do not have cellphone facilities